Hydrological Characteristics of Tigris River Flooding in Iraq - Abdul Wahid Gutami , Prof. Assist .Dr. Hussein (Basra studies journal, 2024)
During the period (1988-2020), wet years in the Tigris River basin are marked by a significant increase in water inflows and rapid peak timing. Analyzing the hydrological characteristics of these wet years, including flood levels and discharge characteristics (annual, seasonal, and monthly), is essential for illustrating the variability in water inflows. This research aims to analyze exceptional annual water inflows recorded within the Tigris River basin (Iraq) during the period (1988-2020) and compare the water inflows of two flood years (1987-1988 and 2018-2019). Additionally, it examines the economic, social, and environmental impacts of the 2018-2019 water year floods on the river basin. Such studies are of critical importance for mitigating the effects of peak flood waves and reducing their impact on development projects within the basin.